Depression, sleep quality and condom use amongst Iranian people living with human immunodeficiency virus - Marzieh Mahboobi; Arezu Najafi; Amin Nakhostin-Ansari; Parvin Afsar Kazerooni; Matin Bazargani; Fatemeh Navaiian; Samaneh Akbarpour (AOSIS, 2020)
Background: Depression is a common mood disorder in people living with human immunodeficiency virus (PLWH) and is associated with risk-taking sexual behaviour. Objectives: This study examines depression, sleep quality and condom usage amongst PLWH in Tehran, Iran. Method: This cross-sectional study was undertaken between October and November 2019 on 298 PLWH referred to voluntary counselling and testing centres (VCTs) in Tehran. Participants provided information as per the following questionnaires: the Depression, Anxiety, Stress Scale (DASS), the Pittsburgh Sleep Quality Index Questionnaire and a demographic questionnaire that evaluated condom use. Results: A total of 298 PLWH, of whom 202 (67.8%) were men with a mean age of 39.81 years, were enrolled in the study. The DASS classified 57% with depression. Fewer than 20% of these used condoms regularly. The majority of depressed patients were men (68.6%) and 31.4% were women. The depressed patients were more likely not to use condoms than those who were not depressed (adjusted odds ratio [OR] = 6.5; 95% confidence interval [CI], 3.70-11.42). The adjusted OR for not using a condom amongst the depressed was 7.12 times greater (95% CI, 5.85-10.11) than in those without depression. Conclusion: Our findings suggest that depression is common amongst PLWH in Tehran and is associated with risk-taking sexual behaviour. Appropriate interventions are needed to address mental disorders in PLWH. It is recommended that patients be screened regularly for symptoms of depression and, where indicated, counselled and managed.